Housing Equity Withdrawal: Perceptions of Obstacles among Older Australian Home Owners and associated Service Providers - Jefferson, Therese; Austen, Siobhan; Ong, Rachel; Haffner, M.; Wood, Gavin (2017)
Housing wealth dominates the asset portfolios of the older population in Australia and many other countries. Given the anticipated spike in fiscal costs associated with population ageing, there is growing policy interest in housing equity withdrawal (HEW) to finance living needs in retirement. This paper sheds light on homeowners’ perceptions of the obstacles associated with two forms of HEW: mortgage equity withdrawal (where the in situ home owner increases his/her housing-related debt) and downsizing (where housing equity is released by moving to a lower-valued property). We uncover a series of age-specific barriers impeding older Australians’ use of these forms of HEW through qualitative analysis of semi-structured interviews conducted with home owners and professional service providers in related areas of policy and practice. To that end, we recommend the development of a range of safeguards that will minimise the risk exposure and other obstacles associated with HEW for older home owners.